Design and Performance of Well-Performing Railway Transitions. Issue 1 (2016) - Stark, Timothy D.; Wilk, Stephen T.; Rose, Jerry G.
This paper presents a review of railroad track transition behavior, causes of undesirable transition performance, and designs that have exhibited desirable transition performance as determined by field measurements. The first focus of the paper is a review of common factors that lead to transition geometry deviations. These deviations involve the inherent problem of a train passing from an earthen and ballasted approach to a nearly rigid bridge structure. The differential movement between the earthen approach and bridge usually results in increased dynamic loads. These increased dynamic loads can be avoided if all transient and permanent displacements between the approach and bridge deck are balanced by reducing ballast and subgrade settlements in the approach and decreasing the stiffness of the bridge. Two well-performing bridge transitions were monitored by using noninvasive accelerometers to illustrate design techniques that can balance transition differential movements and thus reduce dynamic loads. Other design techniques and ballast remedial measures are discussed because of their relevance to reducing ballast settlement in the approach.